2017
DOI: 10.1038/ncomms14268
|View full text |Cite
|
Sign up to set email alerts
|

Host-inherent variability influences the transcriptional response of Staphylococcus aureus during in vivo infection

Abstract: The rise of antibiotic resistance calls for alternative strategies to treat bacterial infections. One attractive strategy is to directly target bacterial virulence factors with anti-virulence drugs. The expression of virulence traits by pathogens is, however, not constitutive but rather induced by the level of stress encountered within the host. Here we use dual RNA sequencing (RNA-seq) to show that intrinsic variability in the level of host resistance greatly affects the pathogen's transcriptome in vivo. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 70 publications
1
56
1
Order By: Relevance
“…This could either indicate that SSL3 and SSL4 are expressed but not required for staphylococcal virulence in the mouse model or that they are not expressed at all in this system. Transcriptional data extracted from a large RNA-Seq screen per- formed by Thänert et al [35] in two different mouse strains, using an infection model and bacterial strain similar to our study (http://www.ebi.ac.uk/ena/data/ search?query=PRJEB14649), revealed that in the kidney of mice infected with S. aureus SH1000 no ssl3 or ssl4 expression could be detected ( Fig. 2 b, c), making the latter hypothesis likely.…”
Section: S Aureus Ssl3 Expression Is Low During Both In Vitro Growthmentioning
confidence: 99%
“…This could either indicate that SSL3 and SSL4 are expressed but not required for staphylococcal virulence in the mouse model or that they are not expressed at all in this system. Transcriptional data extracted from a large RNA-Seq screen per- formed by Thänert et al [35] in two different mouse strains, using an infection model and bacterial strain similar to our study (http://www.ebi.ac.uk/ena/data/ search?query=PRJEB14649), revealed that in the kidney of mice infected with S. aureus SH1000 no ssl3 or ssl4 expression could be detected ( Fig. 2 b, c), making the latter hypothesis likely.…”
Section: S Aureus Ssl3 Expression Is Low During Both In Vitro Growthmentioning
confidence: 99%
“…The complex cellular environment of tissue specimens provides a bioinformatics challenge to analysis. Previous dual RNAseq studies of in vitro infected cells have been limited to only one cell type while in vivo studies in mouse models lacked analysis of the tissue cellular environment (Damron et al, 2016;Nuss et al, 2017;Pittman et al, 2014;Thanert et al, 2017). Here, we developed a computational framework that reduces the each disease lesion into a series of scores representing the host cellular immune pathways and pathogen abundance or activity.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of a "dual-RNAseq" approach has recently been applied to simultaneously sequence the transcriptomes of both the host and pathogen organisms in vitro, with subsequent isolation of each transcriptome in silico through alignment of the respective genomes of the organisms (Damron et al, 2016;Niemiec et al, 2017;Nuss et al, 2017;Thanert et al, 2017;Wesolowska-Andersen et al, 2017;Westermann et al, 2016;Zimmermann et al, 2017). The transcriptomes, which can lead to poor coverage of bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bacterial pathogens evolve to use different factors to interplay with the host at different times over the course of a complex infectious cycle (Miller et al , ). Usually, the successful infection is a result of complicated interactions between the time‐resolved factors' expression profile of the pathogen and its microenvironment encountered during infection, but not a single one (Monack et al , ; Thanert et al , ). Therefore, the anti‐virulence strategy can target multiple therapeutic windows to intervene the outcome of an infection, such as targeting bacterial factors mediating adhesion to the host (Krachler & Orth, ), secretion systems (Baron, ), regulatory systems (Rasko et al , ), quorum‐sensing signaling (Starkey et al , ), elements that involved in evading host defense (Wang et al , ), and toxin trafficking and function (Saenz et al , ).…”
Section: Introductionmentioning
confidence: 99%